2003
DOI: 10.1097/00001756-200305060-00022
|View full text |Cite
|
Sign up to set email alerts
|

Morphological decomposition involving non-productive morphemes: ERP evidence

Abstract: It is generally believed that readers decompose a complex word into its constituent morphemes only when those morphemes participate productively in word formation. Here we recorded eventrelated potentials (ERPs) to words (e.g. mu¥er, receive), nonwords containing no morphemes (e.g. £ermuf), and non-words containing a pre¢x and a non-productive bound stem (e.g. in-ceive). Prior work has shown that pronounceable non-words elicit larger-amplitude N400 components than words. If readers treat non-words containing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 19 publications
10
37
0
Order By: Relevance
“…Previous studies revealed similar effects of lexicality (e.g., Carreiras et al, 2005;Hutzler et al, 2004;McKinnon et al, 2003). These studies also found larger negativities for nonwords compared to words starting at 300 ms.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies revealed similar effects of lexicality (e.g., Carreiras et al, 2005;Hutzler et al, 2004;McKinnon et al, 2003). These studies also found larger negativities for nonwords compared to words starting at 300 ms.…”
Section: Discussionsupporting
confidence: 60%
“…the first sub-stage of word form encoding). In addition, the N400 effect has been found to be sensitive to morphological processing in visual word recognition/comprehension (McKinnon et al, 2003). ERP results obtained in the present study are consistent with the ones obtained in Koester and Schiller (2008) and Lensink et al (2014), as an increased amplitude value was found for morphologically primed target words in the latency range 400-550 ms poststimulus.…”
Section: Electrophysiological Analysis Of Morphological Primingsupporting
confidence: 91%
“…In Koester and Schiller (2008) and Lensink et al (2014), using the previously mentioned morphological priming task, the N400 amplitudes were reduced for the morphologically related condition compared to the unrelated one. This corresponds to the language comprehension literature, where evidence has been found that N400 amplitudes are sensitive to morphological processing (e.g., McKinnon et al, 2003). Further evidence comes from a study using intracranial recordings within Broca's area (Sahin et al, 2009) where participants were cued to inflect nouns and verbs.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations